KEANEKARAGAMAN GENETIK Salmonella typhi - Darmawati S (JURNAL KESEHATAN, 2009)
Abstract Strain the bacteria Salmonella typhi (5. typhi) is also called Salmonella choleraesuis serovar typhi, Salmonella serovar typhi, Salmonella enterica serovar typhi including members familia Enterobacteriaceae, have O antigen (somatic), H antigen (flaSel) and capsule antigen (Vi), wide spread around the world. S. typhi have the genetic diversity that can be shown that the dIffirence in sensitivity towards antibiotics that describes the plasmid profiles of diffirences, as well as the diffirences, of each of ribotyping strain originating from a dffirent area, By Knowing the genetic diversity S.typhi bacterial strain can be used as a basis to track the epidemiologt of cases of fever typoid, in addition to the Unique-wilh the unique nature of the bacterial strain can be used as a basis for identification and classification. Keywords: Salmonella typhi, the genetic diversity